Formation of magnetic biskyrmions mediated by an intrinsic emergent monopole-antimonopole pair - Cheng-Jie Wang; Pengfei Wang; Yan Zhou; Wenhong Wang; Fazhan Shi; Jiangfeng Du (npj Quantum Materials, 2022)
Abstract Various properties and potential technological applications of magnetic skyrmions have stimulated a flourishing interest in topological spin textures. Among them, biskyrmions with a rare topological charge of two are observed but their existence is still under debate. In this work, we present the formation of biskyrmion bubbles mediated by emergent monopoles via micromagnetic simulations. We find that biskyrmion bubbles and trivial bubbles share a unified three-dimensional structure, in which the relative position of an intrinsic emergent monopole-antimonopole pair dominates the two-dimensional topological property at the middle plane of magnetic uniaxial films. Biskyrmion bubbles can be transformed from trivial bubbles by the motion of emergent monopoles in confined geometry, paving the way for developing devices. These results highlight the three-dimensional aspect of skyrmion-related nanostructures and the versatile roles of emergent monopoles in topological spin textures.